2014
DOI: 10.4028/www.scientific.net/amm.554.520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biodiesel Derived by Waste Cooking Oil on Fuel Consumption and Performance of Diesel Engine

Abstract: Biodiesel is the alternate fuel which is derived from renewable sources either is vegetable oils or animal fats. For that reason, the vehicle run by Bio-diesel Fuel (BDF) has been a potential option and the alternative sources of fuel are receiving a lot attention in the automotive industry. The use waste cooking oil (WCO) biodiesel as an alternative fuel in engines has advantages from both economic and the emissions of carbon monoxide (CO) and hydrocarbons (HC) in the exhaust gas. Purpose of this study is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…There are many sources and conditions that affect the stability of a combustion system [16][17][18]. Moreover, there are some researchers that focus on controlling the blending of fuel ratio to influence the effect of instability in a combustion system [19][20][21][22][23][24]. This paper reviews focus on to the primary interaction of acoustic perturbation that affect the stability of a combustion system.…”
Section: Introductionmentioning
confidence: 99%
“…There are many sources and conditions that affect the stability of a combustion system [16][17][18]. Moreover, there are some researchers that focus on controlling the blending of fuel ratio to influence the effect of instability in a combustion system [19][20][21][22][23][24]. This paper reviews focus on to the primary interaction of acoustic perturbation that affect the stability of a combustion system.…”
Section: Introductionmentioning
confidence: 99%
“…A thermocouple was used to measure the parameters temperature every 5 minutes interval with the engine operating for an hour under no load, 2.5 kg, 5 kg and 7 kg load condition. The emission performance was run using neem oil blends as samples [17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…Thus, improvement in engine exhaust emissions from biodiesel fuel is urgently required to meet the future stringent emissions regulations. It was reported that the biodiesel properties affect the level of combustion, injection timing and spray pattern, thus causing longer injection duration due to the change in the start of injection [4,5]. This biodiesel has a high cetane number compared to diesel, less sulfur and contains more oxygen, almost 10% oxygen by weight.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, alternatives are based on vegetableoil-based fuel. The key issues in using this fuel are the oxidation stability, the stoichiometric point, the bio-fuel composition, antioxidants on degradation and the volume of oxygen compared to diesel [3][4][5]. In addition, although biofuels are more attractive and economical, they create problems of higher emissions compared with petroleum-based diesel [6][7][8].…”
Section: Introductionmentioning
confidence: 99%